Monitoreo y evaluación de la velocidad vehicular para el control de la misma en la ciudad de Riobamba - Escalante Yépez, Alex Ulises (2022)
According to the (World Health Organization, 2017), speed is one of the leading causes of accidents with fatal consequences. In accomplished studies, the increase of 1 km/h in the average rate of a vehicle causes a rise of 4 to 5% in collisions with fatal consequences. The objective of this research was to monitor and evaluate vehicle speed for speed control in Riobamba city. Using TNS-SV radar equipment, the vehicle speeds were collected on established points. With the help of the Directorate of Management, Mobility, Transit, and Transportation of Riobamba city, the accidentality percent on the issues was found, and it made a comparative analysis between speeds and accidents. Finally, the sites where the maximum speed limits are exceeded were identified.